BIOM-11. THE PROGNOSTIC VALUE OF ROUTINE AND SPECIALIZED BLOOD TESTING IN GLIOBLASTOMA: A SYSTEMATIC REVIEW. (12th November 2021) - van der Boog, Arthur; Cialdella, Fia; Bruil, Danique; Smitt, Karlijn; de Vos, Filip; Verhoeff, Joost
Abstract: BACKGROUND: A combination of clinical characteristics, radiological findings and tissue markers is used in the assessment of glioblastoma prognosis and prediction of treatment response. The value of routine blood tests as a tool of prognosis has been a subject of debate. In addition to increased complication rate in subsequent resections and radiological uncertainty in treatment monitoring, there is a need to monitor tumor markers in a minimally invasive manner, as molecular characterization becomes more important in the management of glioblastoma. The objective of this review is to evaluate the prognostic value of any blood marker during the course of disease and treatment in glioblastoma. METHODS: We researched Pubmed and Embase for clinical studies including cohort studies and randomized controlled trials that included at least 10 adult patients and blood testing during course of disease. We extracted data on clinically relevant endpoints, i.e. overall survival (OS) or progression-free survival (PFS), in accordance with the PRISMA statements. RESULTS: The search strategy yielded 6389 unique articles, of which 150 met the inclusion criteria. 37 studies found an association between survival outcomes and pre-operative markers including complete blood count (erythrocytes and leukocytes with differentiation characteristics), inflammatory markers (erythrocyte sedimentation rate and C-reactive protein), coagulability markers (prothrombin time, activated partial thromboplastin time and D-dimer), albumin, lactate dehydrogenase and glucose. Furthermore, 10 studies reported a correlation between changes in platelets, erythrocytes and leukocytes during course of disease and treatment and OS. Finally, serum and plasma levels of markers including various proteins, microRNAs and microvesicles were associated with PFS and OS. CONCLUSION: The results of this study suggest that routine and specialized blood tests provide additive information on OS and PFS in glioblastoma. These promising findings highlight the need for further investigation of blood testing for biomarker evaluation.